Respostas
respondido por:
1
an = 20
n = 51
r = 5
an = a₁ + (n - 1) * r
20 = a₁ + (51 - 1) * 5
20 = a₁ + 50 * 5
20 = a₁ + 250
a₁ = 20 - 250
a₁ = -230
Espero ter ajudado. Valeu!
n = 51
r = 5
an = a₁ + (n - 1) * r
20 = a₁ + (51 - 1) * 5
20 = a₁ + 50 * 5
20 = a₁ + 250
a₁ = 20 - 250
a₁ = -230
Espero ter ajudado. Valeu!
meotl:
Ajudou sim na parte da resolução porém aqui na minha apostila só tem essas respostas:
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás